Numerical Analysis Effect of Home Roof Design Towards Thermal Comfort of Occupants - Denda Afri Juliadi; Remon Lapisa; Purwantono Purwantono; Hendri Nurdin (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2020)
The cool room temperature is a requirement in the thermal comfort of a building. In earthquake prone areas, building structures should be designed with minimal material weight. Therefore, it is necessary to be aware of an alternative solution to ensure the room's thermal comfort with minimal weight. This research aims to analyze the influence of roof slope 15O, 20O, 25O, 30O, 35O, 40O, and 45O on the comfort of the room and the strength of the building in the house measuring 6 meters x 8 meters x 3 meters. Analysis is done with three software that is SketchUp as a design, CONTAM to analyze air pressure and TRNSYS to simulate all the data that has been created in SketchUp and CONTAM. Obtained the lowest temperature at a roof slope of 45O and the lowest weight is the roof with a 15O slope. Temperatur ruangan yang sejuk merupakan syarat dalam kenyamanan termal sebuah bangunan. Di kawasan rawan gempa, struktur bangunan harus dirancang dengan bobot material yang minimal. Oleh karena itu, perlu dicarikan solusi alternatif untuk menjamin kenyaman termal ruangan dengan bobot yang minimal. Penelitian ini bertujuan menganalisa pengaruh kemiringan atap 15o, 20o, 25o, 30o, 35o, 40o, dan 45o terhadap kenyamanan ruangan serta kekuatan bangunan pada rumah berukuran 6 meter x 8 meter x 3 meter. Analisa dilakukan dengan tiga software yaitu SketchUp sebagai perancangan, CONTAM untuk menganalisa tekanan udara serta TRNSYS untuk menyimulasikan semua data yang telah di buat pada SketchUp dan CONTAM. Didapatkan hasil suhu terendah berada pada kemiringan atap 45 o dan bobot terendah adalah atap dengan kemiringan 15o.